O.J. Zharinov, V.O. Kuts, O.A. Yepanchintseva, G.P. Verezhnikova, L.O. Tkachenko, N.O. Lifantyeva, N.V. Ponych, N.B. Ivanyuk, N.Yu. Vasilyeva - O.J. Zharinov; V.O. Kuts; O.A. Yepanchintseva; G.P. Verezhnikova; L.O. Tkachenko; N.O. Lifantyeva; N.V. Ponych; N.B. Ivanyuk; N.Yu. Vasilyeva (Кардіохірургія та інтервенційна кардіологія)
The article devoted to the 40-years anniversary of the Functional Diagnostics department of Shupyk National Medical Academy of Postgraduate Education, reviews achievements, problems and perspectives of the postgraduate education of the functional diagnostics physicians. It emphasizes the need to improve the legislative base, to modernize the functional diagnostics system in Ukraine and improve the quality of training of the related specialties’ physicians, taking into account the experience of European countries.